TINJAUAN HUKUM KEBIJAKAN PENGHAPUSAN TAGIHAN PIUTANG MACET PADA UMKM DI INDONESIA - Lestari, Tiara Ayu; Safri, Hasan Hamid; Latif, Inas Sofia (LPPM Politeknik Saint Paul Sorong, 2025)
This study aims to analyze the policy of eliminating bad debt bills for MSMEs in Indonesia based on Government Regulation Number 47 of 2024. This policy was initiated as a form of the government's commitment to support the sustainability of MSME businesses that are experiencing financial constraints due to bad loans. The approach used is normative juridical with descriptive-analytical specifications, where research is carried out through the study of documents and literature on primary, secondary, and tertiary legal materials. The results of the study show that this policy has the potential to ease the financial burden of MSMEs by providing ease of settlement of bad credit obligations. However, the effectiveness of the policy is highly dependent on transparent implementation, clear mechanisms, and strict supervision by the government and relevant financial institutions. This policy also faces challenges, especially in reaching MSMEs that are classified as unbanked or unbankable. This study concludes that regulatory updates and more inclusive policy innovations are needed to ensure that the benefits of this policy can be felt by all MSME actors. The integration of financial technology (Fintech) and the improvement of financial literacy need to be optimized to support a more effective and equitable elimination of bad debts.